Relevansi Pemikiran Teologi Islam Muhammadiyah Dengan Pemikiran Pembaharuannya - candra darmawan (Medina-te : Jurnal Studi Islam, 2018)
The spirit of renewal voiced by modernists in the Middle East is so strong that it affects K.H. Ahmad Dahlan to establish the Muhammadiyah organization. Muhammadiyah was established to accommodate and transform ideas for renewal to the people of Indonesia. Muhammadiyah emerged among Indonesian people who experienced anxiety and social, religious, and moral concerns. In understanding the texts of the Koran and hadith and looking for community-oriented values, this organization uses proportional reasoning. However, the appreciation he gave to reason was not as high as the Mu'tazilah as a rationalist. Therefore, Harun Nasution called this organization adhering to the traditional theology style of Ash'ariah. Muhammadiyah's theological thinking is relevant to his renewed thinking. The relevance of his theological thinking with the thought of renewal is seen in two aspects, namely: first, style. Theological thinking and thinking of renewal in the field of law are both traditional in style. The style of his theological thinking is also relevant to his renewed thinking in the religious field which is characterized by revivalism, fundamentalism and purification. Second, the substance of thought. Muhammadiyah's theological thinking about the position of reason, the function of revelation, the concept of faith, free will and predestination, the sending of apostles, sunnatullah, and the anthropomorphism verses are relevant to the thought of renewal in the religious field about ijtihad, criticism of taklid, calls back to the Qur'an and hadith. Muhammadiyah's theological thinking about the position of reason and the sending of the apostle are relevant to the thinking of renewal in the field of education.